Institutions and infrastructure - Ndiershey, Funwie Prosper (KDI School, 2015)
This work starts with an overview of studies that address institutions and or infrastructure concurrently or separately. Using country-level measures of institutional quality and infrastructure from The World Bank’s World Development Index (WDI) dataset, to access the extent to which democracy and the quality of public service delivery eventually lead to a higher quality in tangible infrastructure like road network and access to electricity. Using panel data spanning 142 countries over a time bracket of 14 years, results show that better institutional quality significantly improves the quality of infrastructure. On the other hand, the level of democracy of countries did not significantly affect the quality of their infrastructure. This reaffirms prior findings that the quality of government service delivery outperforms democracy in ramping up the performance of countries; it also reinforces earlier work that suggests that institutions stand as the infrastructure of democracy.
Thesis(Master) --KDI School:Master of Public Policy,2015